2008
DOI: 10.1111/j.1365-3059.2008.01898.x
|View full text |Cite
|
Sign up to set email alerts
|

Causes of incipient rot and rot in regrowthEucalyptus diversicolor(karri) trees

Abstract: Eucalyptus diversicolor (karri) is the second most important commercial timber tree in Western Australia. Sawlogs from regrowth trees often have a discoloration in the heartwood that is more abundant than in sawlogs from mature trees. Other symptoms in regrowth logs include white rot, white pocket rot and brown rot. Fungal isolations and pathogenicity tests were conducted to determine whether this discoloration was incipient rot, and if so, what caused it and which rot(s) would eventually develop. A combined s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…The fastest-growing trees were those most likely to be infected. The fungi most commonly isolated were Stereum hirsutum and Hymenocheate semistupposum (Davison and Tay 2008). No further forest surveys were conducted, but sawmill surveys showed that incipient rot and rot were significantly greater in saw logs from regrowth stands than in those from mature stands (Donnelly and Davison 2008).…”
Section: Incipient Rot In Karri Regrowthmentioning
confidence: 98%
“…The fastest-growing trees were those most likely to be infected. The fungi most commonly isolated were Stereum hirsutum and Hymenocheate semistupposum (Davison and Tay 2008). No further forest surveys were conducted, but sawmill surveys showed that incipient rot and rot were significantly greater in saw logs from regrowth stands than in those from mature stands (Donnelly and Davison 2008).…”
Section: Incipient Rot In Karri Regrowthmentioning
confidence: 98%
“…Thus, managing stands for the persistence and replacement of mature trees may contribute to long-term fuel reduction in Australian forests and woodlands. (Wilson et al 2018, p. 353;SV12) Given relatively slower than expected growth rates in regenerating karri (Prior et al 2011;Wood et al 2015), the presence of Armillaria fungus (Robinson et al 2003) and reduced wood quality (Davison and Tay 2008;Donnelly and Davison 2008), the two-tiered forest available for logging may be fully exploited before regrowth, becoming suitable as saw-logs ( Fig. 5…”
Section: Careful Management Of Old-growth Tofs [Tall Open-forests]mentioning
confidence: 99%
“…In 1986 a large number of fungal isolations were made from rot and discolouration in karri trees (Eucalyptus diversicolor) from regrowth stands in the south-west of Western Australia (Davison and Tay 2008). This was part of a study to determine which fungi caused these symptoms and whether all symptoms of discolouration would ultimately develop into rot.…”
mentioning
confidence: 99%